The spatial distribution of high-season tourism in Poland: based on the records of the 2010 presidential election - Potocki, Jacek (Turyzm/Tourism, 2012)
The 2010 presidential election in Poland was held during the summer season when many voters were away from their place of residence. Data showing the numbers of visitors voting in particular districts were used to identify areas with high tourism intensity. Subsequent analysis showed a very strong concentration and polarization of tourism on the northern and southern margins of Poland and in several big cities.